Implications of the Implementation of the Independent Curriculum for the Development of Students' Talents and Interests - Azizah, Sarmila Yanti; Khairat, Annisaul; Barroso, Uwe; Maja, Gergely (Lingeduca: Journal of Language and Education Studies, 2023)
Technological advances in the world of education have an influence on all aspects related to these educational activities. One of the things that is strongly influenced by the development or advancement of these technologies is the education curriculum. In Indonesia itself, the education curriculum has experienced development from time to time in accordance with the demands of the times. Most recently, Indonesia is now implementing an independent curriculum. An independent curriculum is a curriculum that gives freedom to children regarding their talents and interests in the learning process. The purpose of this research is to find out the implications of implementing the independent curriculum on the development of students' talents and interests. The method used in this research is a qualitative research method with a literature study model. The results of this study are that students' talents and interests have increasingly developed since the implementation of the independent curriculum. Students' talents and interests are more easily identified and developed with this independent curriculum provision. The independent curriculum makes students' talents and interests a reference in determining and compiling teaching materials to suit what students need to follow the learning process.